A special kind of local structure in the CMB intensity maps: duel peak structure - Liu, Hao; Li, Ti-Pei (Research in astronomy and astrophysics, 2009)
P1; We study the local structure of Cosmic Microwave Background (CMB) tem-perature maps released by the Wilkinson Microwave Anisotropy Probe (WMAP) team, and find a new kind of structure, which can be described as follows: a peak (or valley) of average temperature is often followed by a peak of temperature fluctuation that is 4° away. This structure is important for the following reasons: both the well known cold spot detected by Cruz et al. and the hot spot detected by Vielva et al. with the same technology (the third spot in their article) have such structure; more spots that are similar to them can be found on CMB maps and they also tend to be significant cold/hot spots; if we change the 4° characteristic into an artificial one, such as 3° or 5°, there will be less "similar spots", and the temperature peaks or valleys will be less significant. The presented "sim-ilar spots" have passed a strict consistency test which requires them to be significant on at least three different CMB temperature maps. We hope that this article could arouse some interest in the relationship of average temperature with temperature fluctuation in local areas; meanwhile, we are also trying to find an explanation for it which might be important to CMB observation and theory.